OECD Structural Analysis Databases: Sectoral Principles in the Study of Markets for Goods and Services - M. D. Simonova (Vestnik MGIMO-Universiteta)
This study focuses on the characteristics of the information database of the OECD structural business statistics in the analysis of markets of goods and services, and macroeconomic trends. The system of indicators of structural statistics is presented in OECD publications and on-line access to a wide range of users. Collected data sources generated by the OECD offices are based on the national statistical offices of country-members, Russia and the BRICS. Data on the development of economic sectors are calculated according to the methodology of individual countries, regional and international standards: annual national accounts of countries, annual industry and business surveys, methodology of short-term indicators, statistics of international trade in goods. Data are aggregated on the basis of complex indicators statements of the enterprises' questionnaire and business surveys. Information system of structural statistics which is available and continuously updated, has certain features. It is composed of several subsystems: Structural Statistics on Industry and Services, EU entrepreneurship statistics, Indicators of Industry and Services, International Trade in Commodities Statistics. The grouping of industries is based on the International standard industrial classification of all economic activities (ISIC). Classification of foreign trade flows is made in accordance with the Harmonized system of description and coding of goods. The structural statistics databases comprise four classes of industries' grouping according to the technology intensity. The paper discusses the main reasons for the non-comparability of data in the subsystems in certain time intervals.